Inhibition of Replication of Lactic Dehydrogenase Virus by Actinomycin - Yamazaki, Shudo (1973)
Lactic dehydrogenase virus replicated rapidly in monolayers of primary mouse embryo cells and reached a titer of 10(8) mean infective dose per ml within 18 h after infection. Despite the high virus yield, cytopathology was not observed. Examination of the tissue culture media failed to reveal any evidence of interferon, but the virus was found to be as sensitive to mouse interferon as vesicular stomatitis virus. Incubation of mouse embryo cells with actinomycin D markedly inhibited viral replication, whereas cytosine-β-d-arabinofuranoside and 5-fluorodeoxyuridine had no effect on replication. These findings indicate that new DNA synthesis is not required but suggest that the intact function of cellular DNA may be required for lactic dehydrogenase virus replication.